2010 International Conference on Artificial Intelligence and Computational Intelligence 2010
DOI: 10.1109/aici.2010.276
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Self-organizing Map for Clustering Algorithms in Programming Codes

Abstract: The growing self-organizing map (GSOM) is a variation of the popular self-organizing map (SOM). It was developed to address the issue of identifying a suitable size of the SOM, which is usually concerned with vectorial items. To deal with algoritms implemented as programs, which are hardly represented by vectors, a new version of GSOM for clustering non-vectorial items (GSOM/NV) is proposed here. By syntax analysis, source codes of programs are converted into syntax trees, on a basis of which similarities betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Additionally, SOMs have been used to group procedures with similar properties by identifying common features in software code [12,16]. Furthermore, a study demonstrated that the variation of SOMs can identify algorithms implemented as programs by converting source code into syntax trees and computing similarities between them [17]. In conclusion, the studies suggest that SOMs can effectively analyze and cluster programming code, making them a valuable tool in this domain.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Additionally, SOMs have been used to group procedures with similar properties by identifying common features in software code [12,16]. Furthermore, a study demonstrated that the variation of SOMs can identify algorithms implemented as programs by converting source code into syntax trees and computing similarities between them [17]. In conclusion, the studies suggest that SOMs can effectively analyze and cluster programming code, making them a valuable tool in this domain.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Ekstraksi ciri akan menampilkan pola kemunculan k pada suatu waktu dalam suatu sekuens. Pra proses data dilakukan Untuk mencegah adanya hasil implementasi yang bias, maka pengelompokan fragmen metagenom didahului dengan [16]. normalisasi data hasil ekstraksi fitur.…”
Section: Gambar 2 Metodelogi Penelitianunclassified
“…At the data integration stage, intermediate data integration technology such as non-negative matrix factorization methods used in studying disease-disease association and human chromatin interaction can be adapted to minimize information loss [ŽJL + 13, ŽZ15, LDVZK19].More similarity metrics can be introduced into detecting patient similarity, especially supervised and semi-supervised methods. At the neighborhood/cluster detection stage, many advanced technologies like growing SOM and semi-supervised clustering can be utilized [KMJRW14,ZZ10]. One important field to which patient similarity network could make a contribution to precision medicine which can be considered a special type of personalized data science.…”
Section: Clustersmentioning
confidence: 99%